Fission Yeast NDR/LATS Kinase Orb6 Regulates Exocytosis via Phosphorylation of the Exocyst Complex - Ye Dee Tay; Marcin Leda; Christos Spanos; Juri Rappsilber; Andrew B. Goryachev; Kenneth E. Sawin (Cell Reports, 2019)
Summary: NDR/LATS kinases regulate multiple aspects of cell polarity and morphogenesis from yeast to mammals. Fission yeast NDR/LATS kinase Orb6 has been proposed to control cell polarity by regulating the Cdc42 guanine nucleotide exchange factor Gef1. Here, we show that Orb6 regulates polarity largely independently of Gef1 and that Orb6 positively regulates exocytosis. Through Orb6 inhibition in vivo and quantitative global phosphoproteomics, we identify Orb6 targets, including proteins involved in membrane trafficking. We confirm Sec3 and Sec5, conserved components of the exocyst complex, as substrates of Orb6 both in vivo and in vitro, and we show that Orb6 kinase activity is important for exocyst localization to cell tips and for exocyst activity during septum dissolution after cytokinesis. We further find that Orb6 phosphorylation of Sec3 contributes to exocyst function in concert with exocyst protein Exo70. We propose that Orb6 contributes to polarized growth by regulating membrane trafficking at multiple levels. : NDR/LATS kinases are known primarily for their role in controlling cell and tissue proliferation and morphogenesis, e.g., via regulation of transcription in the Hippo pathway. Using fission yeast S. pombe as a model system, Tay et al. show that the NDR/LATS kinase Orb6 is a major regulator of exocytosis. Keywords: Orb6, NDR/LATS kinase, Cdc42, phosphoproteomics, exocytosis, exocyst, Sec3, phosphorylation, fission yeast, Schizosaccharomyces pombe